PENGARUH TINGKAT PERPUTARAN KAS, PERPUTARAN KREDIT DAN TINGKAT PERTUMBUHAN SIMPANAN TERHADAP PROFITABILITAS DI LPD SEKECAMATAN SUKAWATI KABUPATEN GIANYAR - Ni Kadek Lilis; I Wayan Widnyana; Gregorius Paulus Tahu (EMAS, 2021)
LPD is a savings and loan business entity owned by Pakraman Village in order to improve the standard of living of the Village community in supporting the development of the Village in particular and national development in general. The continuity of the LPD's operation can be seen from the level of profitability. The level of profitability is influenced by several factors, namely the rate of cash turnover, the rate of credit turnover and the growth rate of deposits. This research aims to test and provide empirical evidence of the effect of cash turnover rates, credit turnover rates and savings growth rates on the profitability of LPDs in Sukawati District. The population used in this study were all LPDs in Sukawati District. The LPD population in Sukawati sub-district is 33 units which are determined based on the purposive sampling method. The tool used to test the hypothesis is SPSS version 23 For Windows. The results of this study indicate that cash turnover rate, credit turnover rate and deposit growth rate have a positive and significant effect on profitability. LPD management is expected to pay attention to human resource factors in supporting LPD performance so that it can improve performance which can have an impact on increasing LPD profitability.